(untitled) (Research, Society and Development, 2022)
The civil police is the sector of public administration officially responsible for exercising social control and guaranteeing Public Security. The Civil Police Training Course aimed to professionally qualify police officers to work in different sectors of the civil police in the State of Paraíba. As a methodology, expository-dialogued classes were used; exhibition of videos and films for classroom debates, conversation circles, as well as discussion of texts and seminar presentations. The results indicate that customer service is a highly complex service; it is a mediating social activity, aiming to respond to different needs. It is essential to be committed to the work we do, to care for the image of the institution we work for and, above all, to respect citizens regardless of their race, social class, ethnicity and gender. For all these reasons, there is a need for continued professional training, covering different disciplines, such as Quality of Service, according to the National Curriculum Framework within the scope of Brazilian Public Security.